Regenerating Alveolar Bone for Implant Placement: The Efficacy of Autogenous Mineralized Dentin Matrix—A Systematic Review and Meta-Analysis - Madalena Meném; Alexandre Santos; Paulo Mascarenhas (Applied Sciences)
The preservation of the alveolar ridge has gained increasing importance for various types of rehabilitation, including dental implant placement. Consequently, researchers have explored different bone grafts, such as mineralized dentin matrix grafts. However, a comprehensive review of the efficacy of autogenous mineralized dentin (AMD) for alveolar ridge preservation remains lacking. In this review, we evaluated the efficacy of AMD as a method for alveolar ridge preservation in cases of delayed implant placement. A comprehensive search through PubMed, Google Scholar, Cochrane Library, and B-on repositories was conducted without time constraints up to July 2024 to identify peer-reviewed human studies. These studies assessed the percentage of newly formed bone and residual graft following bone regeneration with AMD grafts after tooth extraction, specifically in the context of delayed implant placement. Our analysis included four selected studies involving 55 patients and 67 sockets. The findings suggest that AMD grafts resulted in an average (and 95% confidence interval) of 43.8% [36.6%, 50.8%] newly formed bone, and delayed implant placement was a feasible surgical option for all patients. Although the available literature is scarce, AMD grafting has yielded promising outcomes as a method for bone reconstruction. Nevertheless, additional randomized controlled trials with larger sample sizes and longer follow-ups are required to substantiate these findings.